Desenvolvimento de nanocápsulas contendo disseleneto de bis (p-metoxifenila): biodistribuição e efeitos em modelos de dor em camundongos - Sari, Marcel Henrique Marcondes (2017)
The chronic pain is a global public health problem and its pharmacological management is still unsatisfactory. The identification of novel molecules to effectively treat chronic pain states remains a major objective in biomedical research. Despite the efforts toward the investigation of novel compounds some limitations related to unfavorable physicochemical characteristics delay their clinical application. The bis(p-methoxyl diphenyl) diselenide [(OMePhSe)2] is an organoselenium compound that elicits antinociceptive action in different animal models of pain but has physicochemical limitations. In view of such condition, technological approaches would be more appropriated in view of overcoming these restrictions and maximizing the (OMePhSe)2 pharmacological potential. In this sense, the nanotechnology field has received special attention because of the benefits that are achieved by encapsulating molecules into nanocarriers system, such as polymeric nanocapsules. Thus, this thesis had as objectives the (OMePhSe)2 polymeric nanocapsules formulation development and characterization, compound tissue biodistribution profile as well as in vitro and in vivo toxicological assessment. Besides, the possible pharmacological potential of the formulations was investigated using animal models of acute, inflammatory and neuropathic pain. The Ethical Research Committee of Federal University of Santa Maria approved all experimental procedures carried out in the present study, which are register under the number 1446300315/2015. The Article 1 demonstrated that the (OMePhSe)2 polymeric nanocapsules formulation (poly(Ɛ-caprolactone)+medium chain triglycerides) had appropriated physicochemical characteristics (nanometric size, low polydispersity values, negative zeta potential and neutral pH values), high encapsulation efficacy and chemical stability. The formulation had low toxicological potential in both in vitro (hemolysis assay) and in vivo experiments, which was evaluated using a repeated administration schedule (25 mg/kg/day during 7 days, by the intragastric route). Furthermore, the (OMePhSe)2 incorporation into nanocapsules increased the compound biodistribution profile (kidneys, liver and plasma) in comparison to its free form, suggesting an improvement in its oral bioavailability. In Article 2, the experiments further physicochemically characterized the (OMePhSe)2 nanocapsules (spherical shape and high thermal stability) and demonstrated that the compound nanoencapsulation positively influenced in its pharmacological profile. The hot-plate test was used to assess the (OMePhSe)2 antinociceptive action, which was increased and prolonged by its incorporation into the nanostructures regardless the administration route (intragastric, intraperitoneal and subcutaneous) and regimen schedule (single or repeated administration), suggesting that the expanded tissue (OMePhSe)2 biodistribution profile provided by its nanoencapsulation could improve the pharmacological action. Following, the Manuscripts 3 and 4 investigated the (OMePhSe)2 effectiveness in animal models of inflammatory pain induced by complete Freund’s adjuvant and neuropathic pain induced by the partial sciatic nerve ligation. The compound nanoencapsulation improved and prolonged its anti-hypernociceptive action in the von Frey hair test (Manuscripts 3 and 4). The nanoencapsulation also provided superior anti-inflammatory effect in comparison to the free compound form. The (OMePhSe)2 nanocapsules reduced the paw edema, attenuated the histological impairments and restored the increased myeloperoxidase activity (Manuscript 3). Moreover, these studies revealed that the (OMePhSe)2 treatment, independent of the compound form, restored the mitogen-activated protein kinase pathway activation (p38, ERK1,2 and JNK) (Manuscripts 3 and 4), and the increase in the inflammatory (iNOS, COX-2, Nf-κB, IL-1β and TNF-α)(Manuscripts 3 and 4) and apoptotic proteins content (PARP, bax and bcl-2) (Manuscript 4) evaluated by western blotting technique in samples of cerebral cortex. Therefore, the results of this thesis clearly contemplates an innovative and promising approach to future studies toward the (OMePhSe)2 therapeutic application in the management of pain and inflammatory diseases.